ABORSI DAN KESEHATAN REPRODUKSI - Gani, Husni Abdul (IKESMA, 2010)
Abortion was usualy taken for unwanted pregnancy. For married woman, the reason which emerges is already got children, and economically, couldnât afford them. So the couple decides to have abortion. It is taken by single women, because of free seks relationship. Abortion has conducted by the rape victims also. They have to do abortion because they donât want to have a child that makes them remind about the accident. Unconsciously abortion has various risks, which are a psychological risk and a physical one. Keyword: Abortion, Abortion Method and Risk